Mechanism of in-situ formation of spinel and its effect on the mechanical properties of Al2O3–C refractories. Issue 6 (15th March 2023) - Liu, Guoqi; Li, Hongxia; Zheng, Han; Qian, Fan; Ma, Weikui; Yang, Wengang
Abstract: This work looked at the in-situ formation mechanism of magnesia alumina spinel in Al2 O3 –C refractories with magnesia addition at different firing temperatures. A comprehensive study on the mechanical properties of Al2 O3 –C refractories was performed in comparison to traditional analogs. The magnesia alumina spinel was in-situ formed at the firing temperature of 1150 °C in Al2 O3 –C refractories. With the increase of the firing temperature, the Al2 O3 phase was gradually dissolved in spinel phase to form aluminum rich spinel phase, resulting in a decrease in its lattice constant due to the defects formation. The formed spinel phase was homogenously distributed and bonded well with corundum, improving the interfacial bond, load transferring capacity and crack propagation resistance. The formation of spinel phase also enhanced the sintering of the alumina matrix owing to the solid solution of alumina in the spinel. Therefore, the mechanical properties such as cold modulus of rupture and hot modulus of rupture in Al2 O3 –C refractories achieved a substantial enhancement compared with traditional refractories.